Role of cultural landscape in improving the identity of the Kuala Terengganu town centre as a Malay historic town - Mohd. Ariffin, Noor Fazamimah (2007)
A cultural landscape reflects the symbiotic relationship between man and nature in creating an identity to his living environment. Understanding the Malay cultural landscape is an integral part of the process of examining and appreciating Malaysia’s cultural diversity. The main objective of this study is to identify the character of Malay cultural landscape in the Kuala Terengganu town centre and the factors influencing the formation of such a landscape, which in turn, determines the identity of the place. Based on literature review, the historical background, physical entities and non-physical entities are significant components of Malay cultural landscape. According to history, and field observation, the old town centre of Kuala Terengganu exhibits characteristics of a traditional Malay town as does the old town centre of Kota Bharu. With modern development, the original characteristics of Kuala Terengganu town centre have changed, albeit adversely. This problem is compounded by the lack of awareness on the part of local communities and other relevant authorities on the importance of conserving and protecting these cultural landscapes. The study area has a strong historical background, but its existing physical and non-physical elements badly needing restoration, conservation and preservation efforts. Several recommendations are made to improve the character of Malay cultural landscape and overcome problems of Malaysian urban identity in general. The recommendations also cover restoration of Malay urban characteristics and strategies to arrest deterioration of quality of life of the inhabitants. The criteria for restoration and preservation programmes identified in the study would be useful to develop new townships in Malaysia.